Polarization-enhanced photoelectric performance in a molecular ferroelectric hexane-1, 6-diammonium pentaiodobismuth (HDA-BiI5)-based solar device. Issue 2 (7th January 2020) - Liu, Xinyue; Zhang, Ganghua; Zhu, Mingjun; Chen, Wenbo; Zou, Qi; Zeng, Tao
Abstract : Molecular ferroelectric HDA-BiI5 has been utilized as the light-absorbing layer for organic-inorganic hybrid solar cells. Abstract : Molecular ferroelectric HDA-BiI5 has been utilized as the light-absorbing layer for organic–inorganic hybrid solar cells. Impressive polarization-induced enhancement of photoelectric performance has been achieved in the HDA-BiI5 -based solar device with a fast response time (∼0.64 ms). This work may provide new perspectives for molecular ferroelectrics in photovoltaic and photodetector applications.